Distributed Lags, Morishima Matrices, and the Stability of Economic Models - Tarr, David G. (Econometrica, 1976)
The following sections are included:INTRODUCTIONSTABILITY OF DISTRIBUTED LAG MODELS IN THE MORISHIMA CASECONCLUSIONS AND EXTENSIONSREFERENCES(This abstract was borrowed from another version of this item.)